Reconstruction of Bankruptcy Law for State-Owned Enterprises and Private Enterprises in the Perspective of Economic Justice - Siringoringo, Naek Mampetua; Israhadi, Evita Isretno (Jurnal Greenation Sosial dan Politik, 2025)
The current bankruptcy legal system in Indonesia shows inequality in treatment between State-Owned Enterprises (SOEs) and private companies, especially in terms of filing bankruptcy applications. In practice, SOEs often receive stronger legal protection than private companies, both because of their status as managers of public interest and government policy interventions, which give rise to economic injustice and inequality. The purpose of this study is to critically examine the differences in regulation, implementation, and propose legal reforms that ensure fairness in bankruptcy filings for SOEs and private companies. This research uses a juridical-empirical approach with reference to the theory of legal minds, legislation theory, and development law reform theory. The results of the study show that the bankruptcy arrangement for SOEs and the private sector does not reflect the principles of justice and equality before the law, because there are significant differences in treatment in submission procedures and requirements, as well as the intervention of state actors against SOEs. Legal reconstruction is needed so that bankruptcy regulations are fairer and more accommodating to dynamic economic needs, while maintaining national stability and legal certainty. The conclusion of this study is that Indonesia's bankruptcy system requires comprehensive reform based on substantive justice values, so that law is not only a technical instrument, but also a social engineering tool towards national economic balance.